Alejandro Hernández, Amarás a Dios sobre todas las cosas (Altre Modernità, 2014)
Alejandro Hernández,Amarás a Dios sobre todas las cosas(Ciudad de México, Tusquets, 2013, 313 pp.ISBN 978-607-42-420-8)por Anamaría González Luna C.